Memória, identidade e fronteira: narrativas musicais sobre a tríplice fronteira Brasil / Paraguai / Argentina (1960-2017) - Gonzalez, Emilio (2018)
This research analyzes social practices, memories and narratives produced by musicians that are living (or have lived) in the triple border region between Brazil / Paraguay / Argentina, since the 60s to the present. The hypothesis that we seek to develop suggests that these people are producing memories and musical identities from their movements within those frontiers, constructing own ways of elaborating their experiences . These ways have found in music the means to express their new identities and memories. In order to undertake this work, we have dialogued with oral testimonies (interviews) of some musicians who have crossed the border in the last decades, as well as consulted other materials such as songs and compositions of those authors, articles and interviews, all published in newspapers of the frontier region, as well as other materials obtained from the musicians themselves (records, booklets, photographs, publicity materials, etc.) We also have dialogued with some authors (historians, anthropologists, memorialists, journalists, etc.) who sought to produce and analyze images and discourses about the triple frontier and the historical and social processes that shaped it since the end of the 19th century. Acting autonomously, the musicians and artists, within that frontier, have moved from their own issues, interests and needs , sometimes proposing and achieving transnational aesthetic and stylistic hybridizations and experimentations, sometimes reaffirming "national" identity elements, or proposing identity syntheses. Thus, even with no intention, they ended up being part of the debates that reaffirmed the frontier, operating as factors of invention and having the regional popular music as an important interlocutor and vector